Oral sensations among individuals with illicit drug dependence in rehabilitation centers: A cross-sectional study - Lipsa Bhuyan; Roquaiya Nishat; Balasubramanya Goutham; Kailash Chandra Dash; Pallavi Mishra; Niva Mahapatra (Wolters Kluwer Medknow Publications, 2021)
Background: In developing countries like India, irrespective of the various government laws and actions, substance abuse is a growing problem. Individuals with illicit drug dependence face social and psychological stigma with considerable health problems. Negligence to oral hygiene and lack of oral health treatments intensifies the sensations experienced by the subjects. Aim: The aim is to determine the patterns of substance abuse and oral health sensations among individuals with illicit drug dependence. Materials and Methods: A cross-sectional study was conducted wherein 213 male individuals with illicit drug dependence history, admitted in rehabilitation centers of Bhubaneswar, formed the study population. Information pertaining to the type and duration of drug dependence along with oral sensations experienced by the individuals during a period of 3 months was obtained by interviewing by the subjects. Chi-square test was done to identify variations in oral sensations produced by different illicit drugs and its relationship with their usage pattern. Results: About 40.8% of dependents reported cannabis intake, thus making it the most commonly consumed drug. About 80.8% of all the subjects reported dryness of the mouth, 47.9% reported sensitivity of teeth and 28.2% suffered from the numbness of their mouth. About 19.7% of the individuals felt like chewing on something, 23% inclined toward grinding, whereas 11.7% experienced pain in the jaw muscles and joint. Sixty percent of substance dependents who smoked drugs had sensitive teeth (P ≤ 0.05). All the oral sensations experienced were significantly more among drug dependents with a history of illicit drug usage for >5years in comparison to others. Conclusion: Substance abuse results in a range of oral sensations. De-addiction programs in India lack oral health-care components. Studies on oral complications related to addiction stresses on the need of oral healthcare at various levels, including education, prevention, and treatment. All these components should be amalgamated into general care services for addicts.